L’histoire familiale dans les écrits d’assistance éducative - Carol Bizouarn (Sociétés et Jeunesses en Difficulté)
How family history is referred to in « educational assistance » writings                The French procedure of « educational assistance » requires the juvenile court to order educative measures as soon as it is assumed that the child is in danger within his own family. According to the French civil law, the notion of danger is the very condition of the action of the magistrate in such a matter but there is no precise definition of danger; the law only mentions that the action of the judge is well-founded if « the health, the security, the morality and the conditions of education of the child are seriously endangered ». In such a context, how is family history referred to by social workers, in order to back up the notion of danger ?To answer to that question, the court records of a family known over 3 generations have been examined. The analysis of the first writings (« signalements ») mentioning an actual danger and requiring “educational assistance” shows that references are systematically made to the the child’s siblings’ institutional history, rather than to the previous generations’. On the other hand, very few of the family history itself is mentioned.We can also observe a subtle evolution in the writings made in the course of the assistance. First, the social workers and the family are expecting from each other to acknowledge their own model of education, both sides confronting their representations of parenthood. Then comes the time when both parents and social workers bring themselves to accept the others with their own specific representations of how to act like parents. At the same time there is a second process at work. References to previous events or behaviours are progressively rubbed out from the children’s record, as they become parents themselves; then the source of danger is removed from the adults’ side to the children’s. Thus, in the concern about having an objective analysis of the present situation, the social worker eliminates all historical arguments from his reasoning, just as if he now regarded these previously alleged elements of danger as irrelevant.